Rationale and design of a randomized placebo-controlled trial assessing the effects of etiologic treatment in Chagas' cardiomyopathy: the BENznidazole Evaluation For Interrupting Trypanosomiasis (BENEFIT) - Marin-Neto, José Antônio (2008)
Fil: Marin-Neto, José Antônio. Medical School of Ribeirao Preto, University of Sao Paulo, Ribeirão Preto, Sao Paulo; Brasil.